Selective arterial embolization with adipose tissue - Reyes, Ismael; Villar, Miguel; Grillo, Bartolomé; Penco, Ernesto; Ramírez, Wilson; Tellechea, Miguel; Purriel, Juan (Cirugía del Uruguay, 1977)
In view of current clinical application of selective arterial embolization in certain tun:ior pathologies, arterio-venous malformations and/or acute hemorrhages, experimental work has been conducted with adipose tissues as occlusive agent, using renal arterial territory as the parenchyma far testing its effects. The_ study was divided into two series: the first had a survival rate of 24 hrs. and the second, between 7 and 13 days. Post-embolization angiographic and anatomopathological controls were performed and in both series conclusive radiological and histological documentation was obtained which proved that obstruction had been achieved with the embolized material under study.